Organic Waste Processing System Innovation with Ergonomic Composter - Fajarwati Ibnu, Indra (OJS Universitas Muhammadiyah Gresik, 2024)
Activity empowerment public form socialization technology about making fertilizer composter is as effort For utilise potency waste kitchen House ladder in the form of organic waste. Rubbish organic is rubbish Which contain rate water tall And young rotten. Stacking rubbish organic can pollute environment And become epidemic disease.One method For process rubbish organic is making fertilizer compost. This activity was carried out in Dermo Village Benjeng District, Gresik Regency. The method used in this activity is providing materials by means of outreach to residents, especially to the Village Head Dermo, RT head, RW head, BPD, Cadre Women and Dermo Village Youth Organization. Giving material about various material remainder rubbish organic around environment House Ladders that can be used as a source of raw material for making compost. Socialization is carried out by practicing designing tools for making fertilizer compost with use material standard greenery/foliage, hump banana, And dirt cows, which were found in abundance around the household, were then added with fertilizer Which Already So, fluid EM4 (For plant) And water enough. Transfer technology making fertilizer compost give benefit Which big that is exists increasing residents' knowledge about the benefits of leftover organic waste as materials standard making compost fertilizer.